2017
DOI: 10.1002/jib.446
|View full text |Cite
|
Sign up to set email alerts
|

Comparative shelf life study of two different rice beers prepared using wild-type and established microbial starters

Abstract: A mixed dough fermentation culture (Hamei) is used to inoculate the traditional rice beer Atingba in Manipur, India. Lactic acid bacteria and yeast were isolated from Hamei and, using rDNA sequencing, shown to be Pediococcus pentosaceus and Pichia anomala. Two black rice beers were produced, one (BS‐1) with Aspergillus oryzae, Saccharomyces cerevisiae and Lactobacillus plantarum and the other (BS‐2) with P. pentosaceus, P. anomala (from Hamei) and A. oryzae. After fermentation for 9 days the beers were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In a study, probiotic bacteria such as Pediococcus pentosaceus and Pediococcus anomala strains were isolated from Hamei , an ethnic rice beer (called Atingba ) fermentation culture of Manipur, India. The use of these microbes in the starter showed positive effect on the beer quality with an overall improvement in terms of their microbiological properties as well as biochemical properties ( Mangang et al, 2017b ). During the 3 months that the beers were stored, there was a greater inhibition of lipid peroxidation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study, probiotic bacteria such as Pediococcus pentosaceus and Pediococcus anomala strains were isolated from Hamei , an ethnic rice beer (called Atingba ) fermentation culture of Manipur, India. The use of these microbes in the starter showed positive effect on the beer quality with an overall improvement in terms of their microbiological properties as well as biochemical properties ( Mangang et al, 2017b ). During the 3 months that the beers were stored, there was a greater inhibition of lipid peroxidation.…”
Section: Methodsmentioning
confidence: 99%
“…During the 3 months that the beers were stored, there was a greater inhibition of lipid peroxidation. As a result, the beers differ depending on the type of microbial starter employed, with wild-type cultures being preferred ( Mangang et al, 2017b ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that more inhibition of lipid peroxidation during the 3 rd month of fermentation observed the diferent shelf-life of the beverages. Te shelf-life of Manipuri rice beverage, Atingba, can be increased up to 3 months at 32 °C [129]. Studies revealed that it is used as a natural preserving agent and food supplement.…”
Section: Stability and Risk Factors Associated With Alcoholic Ferment...mentioning
confidence: 99%